A CROSS-SECTIONAL ASSESSMENT ON SOLID WASTE MANAGEMENT PRACTICES IN MUBENDE MUNICIPALITY, UGANDA. - Kalyango, Benedict; Lujjimbirwa, Fortunate; Kaweesa, Simon Peter; Kalukusu, Amos Ronald; Odoki, Martin (Student’s Journal of Health Research Africa, 2024)
Background: Mubende Municipality is a developing municipality located in Uganda’s central region. As a result of urbanization, the human population has increased. The rise in population due to industrialization and farming has resulted in increased municipal solid waste (MSW) accumulation. The purpose of this study was to assess solid waste management practices in Mubende municipality, Mubende District. Methods: A cross-sectional descriptive design was employed in the study. The South Division, West Division, and East Division are the three municipal divisions where the study was conducted. A simple random sampling technique was used in the investigation to select 400 respondents at random from each of the three divisions. The study’s data was collected through observations, interviews, and questionnaires. Data were analyzed using descriptive statistics. Results: The sources of MSW in Mubende District were 50.5% households, 21.5% markets, 13.25% commercial areas, 11.5% industries, and 3.25% institutions. Organic waste accounts for the majority of solid waste generated in Mubende (34.50% agricultural waste and 23.0% food waste). Food scraps from households made up 23.00% of municipal solid waste. Plastics and polythene are also considered solid waste accounting for 16.75% and 13.75% respectively. The most common methods of waste management were landfills 45% and burning 27.50%. Conclusion: Organic waste accounts for the majority of solid waste generated in Mubende Municipality. Mubende Municipality’s preferred solid waste management methods are landfilling, open burning, composting, and indiscriminate dumping. However, these methods are frequently mismanaged, as evidenced by the visible heaps of rotting garbage and scattered and uncollected solid waste. Recommendation: Mubende Municipality officials should consider building and maintaining solid waste collection points to prevent waste from spreading throughout open spaces, streets, and water streams. This will reduce the amount of solid waste dispersed and the resulting unsanitary conditions at central collection sites.